Information technologies in training process modelling - Plećaš Jovan (University Educons, Faculty of Sports and Tourism, Novi Sad, 2019)
The use of increasingly advancing information technologies (IT) in sports has reached a high level in the past few decades and has enabled obtaining data that are more valid, reliable and timely. Inertial sensors are used to gather information on athletes' movement, speed, acceleration and distance covered, and cameras that use light detection to calculate the 3D position of markers are used to capture and analyse movement and are considered a "gold standard" in this field. Wearable devices detect and analyse data against internal or external parameters they monitor, so physiological parameters such as heart rate, muscle oxidation level and body temperature can be monitored in real time, on a smartwatch or a phone. Virtual reality is used in training processes of athletes, most often during psychological and tactical preparations, as well as in learning and practicing of movements. Coaches and athletes are thus able to receive accurate data in real time outside the laboratory conditions and plan and adjust the training process accordingly. The goal of this paper is creating an overview of the most important information technologies used in modelling of training processes.